Violet light could improve sleep quality and blood glucose levels in healthy individuals: A pilot study - Tomonobu Kato; Yasue Mitsukura (PLoS ONE, 2025)
Light is perceived through the retina, the light-sensing tissue layer of the eye, and can directly influence the brain. Light exposure triggers various biological responses that improve sleep quality and stabilize mood. Recently, violet light, exhibiting a unique wavelength of 360–400 nm, has garnered significant attention due to its perception through a specific receptor, marking a novel research area. Herein, we used “violet light glasses” that directly emit violet light into the human eye and investigated their effects on healthy humans in real-life settings. This study demonstrated that two hours of violet light exposure in the morning enhanced sleep quality in approximately 20% of the healthy participants and was also associated with improved blood glucose levels. Although this was a pilot study due to its small sample size, our findings indicate that violet light could potentially promote health benefits in humans.